The Sound of William Barnes's Dialect Poems: 3. Poems of Rural Life in the Dorset Dialect, third collection (1862) - Burton, T. L. (University of Adelaide Press, 2017)
"This is the third volume in a series that sets out to provide a phonemic transcript and an audio recording of each individual poem in Barnes's three collections of Poems of Rural Life in the Dorset Dialect. With 96 poems in an astonishing variety of metrical forms, the volume includes some of those that are most loved and admired: poems of tragedy ("Woak Hill", "The turnstile") and comedy ("John Bloom in Lon'on", "A lot o' maïdens a-runnèn the vields"); celebrations of love anticipated ("In the spring") and love fulfilled ("Don't ceäre"); protests against injustice and snobbery ("The love child"); struggles to accept God's will ("Grammer a-crippled"); and poems on numerous other subjects, with an emotional range stretching from the deepest of grief to the highest of joy."